“THIS NEW ATTEMPT AT REBELLION IN MEXICO WILL NOT BE MORE SUCCESSFUL THAN THE PREVIOUS ONES”: ACCOUNTS OF THE AUSTRIAN DIPLOMATS IN SPAIN ON THE INDEPENDENCE OF MEXICO(1820-1823) (Tzintzun, Revista de Estudios Históricos, 2024)
The article is based on the diplomatic documentation that the representatives ofthe Austrian Empire in Madrid sent to Vienna between 1808 and 1825. Althoughthey would refer to the events in Mexico, they didn’t describe them asindependence movements. Until 1820 they didn’t show the conviction of a realand absolute independence, but from 1822 on they already made it clear that thesituation had changed to the point of even thematize the recognition of theindependence. The latter became widespread in Europe after 1823 and madeAmerica a subject of the monarchical politics of the time.
Keywords: Austrian Diplomacy in Spain; Independence of Mexico; Iturbide; Metternich Spanish Monarchy